Simultaneous Detection of Group A Rotavirus in Swine and Rat on a Pig Farm in Brazil - Paloma de Oliveira Tonietti; Aline Santana da Hora; Fernanda Dornellas F. Silva; Karen Linares Ferrari; Paulo Eduardo Brandão; Leonardo José Richtzenhain; Fabio Gregori (The Scientific World Journal)
This study investigated the occurrence of rotavirus in porcine and Rattus norvegicus, at the same time, on a pig farm in the city of Jaguariúna, São Paulo, Brazil. Swine () and rat () fecal samples were analyzed by nested RT-PCR assay. Rotavirus occurred in seven porcine and two rat samples. A total of three pig and one rat samples were further submitted to genetic sequencing. The partial NSP5 gene phylogeny showed that all strains were segregated in the genotype H1. These results point toward a cross-species transmission between rats and pigs on the surveyed farm and represent the first detection of rotavirus in Rattus norvegicus in Brazil.